A qualitative exploration of how the COVID-19 pandemic shaped experiences of self-managed medication abortion with accompaniment group support in Argentina, Indonesia, Nigeria, and Venezuela. Issue 1 (31st December 2022) - Bercu, Chiara; Filippa, Sofia; Jayaweera, Ruvani; Egwuatu, Ijeoma; Nmezi, Sybil; Zurbriggen, Ruth; Grosso, Belen; Kristianingrum, Ika Ayu; Maneiro, Mariana; Liparelli, María Soledad; Sandoval, Stephhanie; Tapia, Isha; et al.
Abstract: Globally, people self-manage their medication abortions without clinical assistance. Feminist activist collectives (accompaniment groups) support people through self-managed abortion with evidence-based guidance. We sought to understand the impact of COVID-19 and related restrictions on the need for and experiences of self-managed abortion with accompaniment support across varied legal and social contexts. Between May and October 2020, we conducted in-depth interviews with individuals who self-managed abortions with support from accompaniment groups during the pandemic in Argentina, Indonesia, Nigeria, and Venezuela. We conducted a thematic analysis to understand the impact of COVID-19 on participants' experiences with accompanied self-managed abortions. Across 43 in-depth interviews, participants in all four countries described how the COVID-19 pandemic created challenges at each step of their abortion process, from confirming the pregnancy, accessing abortion pills, finding a private, comfortable place, and verifying abortion completion. For most people, conditions related to the pandemic made it harder to self-manage an abortion; for a minority, being at home made aspects of the experience somewhat easier. Nonetheless, all participants reported feeling supported by accompaniment groups, and COVID-19 and related lockdowns reinforced their preference for accompaniment-supported self-managed abortion. These findings highlight the essential role that accompaniment groups play in ensuring access to high-quality abortion care in a multiplicity of settings, particularly during the COVID-19 pandemic. Efforts are needed to expand the reach of accompaniment groups to increase access to the high-quality abortion support they provide, filling a critical gap left by health systems and legal infrastructure.